Intraductal papillary mucinous neoplasms of the pancreas – a cost-effectiveness analysis of management strategies for the branch-duct subtype. Issue 12 (December 2018) - Aronsson, Linus; Ansari, Daniel; Andersson, Bodil; Persson, Ulf; Fridhammar, Adam; Andersson, Roland
Abstract: Background: Branch-duct intraductal papillary mucinous neoplasm (BD-IPMN) presents a clinical conundrum. Rigorous long-term surveillance or surgical resection is recommended. The economic consequences of the management have not been fully investigated. Methods: A Markov decision model compared 4 strategies for low-risk BD-IPMN: I = upfront total pancreatectomy, II = upfront partial pancreatectomy, III = initial surveillance, IV = watchful waiting. Surveillance was based on the Swedish Guidelines for Pancreatic Cancer. Probabilities and costs were obtained from the participating unit and from the scientific literature. The incremental cost-effectiveness ratios (ICERs) were calculated and sensitivity analyses were performed by varying relevant parameters. Survival was reported in quality-adjusted life-years (QALYs). Results: Strategy III was the most cost-effective strategy with an ICER of €31 682 compared to strategy IV. Strategy I was the most expensive but yielded the best QALY (9.32). Total number of years, annual risk of pancreatic cancer and annual risk of a low-risk BD-IPMN turning into a high-risk lesion had the greatest impact in the model. Conclusions: Initial surveillance seems to be the most cost-effective strategy in the management of low-risk asymptomatic BD-IPMN. However, the possibility of personalized approaches remains to be investigated.